A wavelet-based method for thrust noise assessment in gravitational wave detection over wide-frequency-range. (August 2022) - Xu, Shuting; Zhang, Zhe; Tang, Haibin; Liang Ling, William Yeong
Abstract: Electric thrusters are considered to be the most promising propulsion system of choice for space gravitational wave detection. However, the requirement of high accuracy and drag-free control results in significant challenges in thrust measurements. In order to detect gravitational wave signals over a wide frequency range, it is necessary to assess the thrust noise of electric thrusters. This paper demonstrates a wavelet-based method for thrust noise evaluation in a time-frequency domain aspect, and aims to expand thrust noise analysis to a wide frequency range from 10 −3 Hz–1Hz. Over this frequency range, a frequency-varying metric boundary is proposed for thrust noise evaluation. This metric boundary is established based on the spectral density of gravitational waves and the time-varying spectrum analysis method, which is used to judge whether the thruster exceeds the requirements for the detection of gravitational waves. A Hall Thruster was ignited and measured experimentally to verify the thrust noise assessment method. The metric boundary evaluates the thrust noise limits in the frequency range from 10 −3 to 1Hz over the entire operating duration to the thruster's power-off period. This time-frequency-varying thrust noise assessment method allows us to identify the time and frequency band within which the electric thruster is capable of exceeding the requirements for gravitational wave detection. Highlights: A thrust noise evaluation method in a wide time-frequency range for use with electric thrusters. A metric boundary for thrust noise judgment is established based on the gravitational waves data. A Hall thruster's thrust noise is evaluated in the frequency range of 10 −3 Hz–1 Hz.